Democracy and international law : an analysis of the origins of democracy, its relationship with international law and its applicability to modern international institutions - Fuller, Roslyn (Trinity College (Dublin, Ireland). School of Law, 2010)
This thesis utilises legal history, comparative law, the law of state organization and international economic law, as well as analyses of political scientists, national and international jurisprudence and original systematic findings to determine the attributes of democracy. Following the introduction (Chapter 1), Chapter 2 of this thesis examines the Athenian democracy (established approximately 2500 years ago, and the only well-studied democracy in the Western world) identifying its basic tenets, modus operandi, and its benefits and deficiencies. Chapter 3 examines the political and legal organisation of the Roman Republic, which developed the rule of law standard now common in Western nations, comparing its development, strengths and weaknesses to those of Athens and, in particular, its compatibility or non-compatibility with the prerequisite conditions of democracy. Chapter 4 briefly investigates the historical development of the legal concept of human rights and their relationship to democracy and the rule of law.
Keywords: Law Ph.D.; Ph.D. Trinity College Dublin.